Analysis of Liquid Volatile Matters from Coconut Shell Pyrolysis by GC-MS and Its Potential as Antifungal Agent - Mashuni; Yanti, N.A.; Jahiding, M.; Kadidae, L.O.; Djaila, R.; Hamid, F.H. (Asian Journal of Chemistry, 2020)
Indonesia is one of the highest producers of coconut in the world and at the same time coconut shell waste is also high. This study used gas chromatography-mass spectrometric (GC-MS) analysis for the liquid volatile matter (LVM) generated from coconut shell pyrolysis and to examine its potential as an antifungal agent. Pyrolysis was performed at 600 ºC. The LVM was 29% (v/w) and had pH 3 and 1.087 g mL-1 density. To determine chemical constituents using GC-MS, the standard NIST MS software was used. The spectrogram analysis of LVM revealed five main compounds, namely phenol (21.92%); (Z)-4-methyl-5-(2-oxopropylidene)-5H-furan-2-one (13.06%); 2,6-dimethoxyphenol (11.54%); 2-methoxyphenol (9.07%) and 2-hydroxy-3-methyl-2-cyclopenten-1-one (7.66%). The LVM showed a excellent fungicidal activity against Phytophthora palmivora at a concentration of 0.125% (v/v).